An integrated data-centric innovations strategy for tackling road safety in Qatar - Adnan Abu-Dayya (16904850) (2015)
The Qatar Mobility Innovations Center (QMIC) has defined an integrated innovations strategy for developing and deploying local solutions and applications that tackle road safety in Qatar and the region. This strategy is based on utilizing distributed data and connected devices to deliver intelligent user-centric services and applications that will tackle different problems contributing to road accidents in Qatar and the region. In this presentation we will review key elements of this strategy, solutions, and applications that have been deployed to-date in Qatar and the ones which are under-development and pilot deployments. In particular, we will highlight the progress made in deploying a national traveler info system for delivering relevant location-based services and alerts, and a national telematics platform and services in support of monitoring driver performance. In addition, we will review the solutions being developed and deployed to minimize the use of mobile phones while driving for both consumers and enterprise segments which are part of the Salamtek (Innovations for Distracted Driving) national initiative which was launched in 2014. Finally, we will discuss the progress made in realizing a connected vehicle program in Qatar (based on using standard-compliant car-to-car and car-to-infrastructure communication protocols and technologies) and the significant potential impact in reducing road accidents in Qatar. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.68